Respiratory Function of University Students Living at High Altitude - Roh, Hyolyun (The Society of Physical Therapy Science, 2014)
[Purpose] This study compared the respiratory function and oxygen saturation levels of university students living at high altitude, to present a new approach for improving respiratory function using high altitudes above sea level. [Subjects and Methods] The subjects were 100 female students attending a university located approximately 850 m above sea level and 104 female students attending a university located at low altitude. Oxygen saturation, heart rate (HR), and respiratory function levels were measured. [Results] For the students living at high altitude, HR, PEF, and FEV1/FVC levels were low. In contrast, their oxygen saturation, FEV1, and FVC levels were higher than the levels found in students living at low altitude. Differences in respiratory function were revealed in first- and second-year students living at high and low altitudes. On the other hand, no significant differences in respiratory function were found between third- and fourth-year students. [Conclusion] University students living at high altitude had a slower HR and higher oxygen saturation levels as well as higher lung and inspiratory capacity levels. Thus, physiological improvement in oxygen saturation levels and pulmonary function were seen in the individuals living at high altitude.